The role of gender and coauthors in academic publication behavior - W. Benedikt Schmal; Justus Haucap; Leon Knoke (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
We use the negotiations for large-scale open-access agreements between German research institutions and leading academic publishers to study how changes in the attractiveness of various journals affect the publication behavior of researchers in economics and adjacent fields. First, as German universities canceled their subscriptions to Elsevier, we study how this affected German economists' incentives to publish in its journals. Second, Springer and Wiley entered into open-access agreements so that researchers in Germany are eligible to publish articles open-access without additional charges for them. Using 243,757 articles published between 2015 and 2022, we find a shift toward included journals, which is most pronounced among women. For Elsevier, the effect is negative and women have a higher tendency to opt out than men. In mixed teams, the dominant gender drives behavior. We conclude that men tend to seek reputation, women visibility. Thereby, female researchers contribute more to the public good of open science. Our findings provide a new explanatory channel of the academic gender gap.
Keywords: A14; I23; J16; L86; Z11; 330; academic publishing; journal choice; gender differences; DEAL; Elsevier; Springer Nature; Wiley; transformative agreements